Emerging vaccine manufacturers are innovating for the next decade. (7th August 2020) - Hayman, Benoit; Pagliusi, Sonia
Highlights: DCVMN members collectively provide over 50% of vaccines supplied to UNICEF. Emerging manufacturers raised their WHO Prequalified vaccines number to over 70. 181 vaccine projects are reportedly in DCVMN members' R&D pipelines. Product innovation and competitiveness will drive the future vaccine supply. Abstract: The Developing Countries Vaccine Manufacturers Network (DCVMN) is a public health-driven alliance consisting of 43 vaccine manufacturers from 14 countries and territories, operating under the mandate to protect all people against known and emerging infectious diseases, by improving the availability of high-quality vaccines globally. The Network provides a platform for organizations to come together regularly to share technical information, best practices and future prospects. DCVMN members are playing an increasingly important role in public health supplying over 50% of the doses of vaccines procured by UNICEF globally. To evaluate the progress made by Network's members, a survey consisting of 9 questions covering three important components of the manufacturers in the network was created, focusing on company dedicated human resources, vaccine production, and research and development efforts. Results show that more vaccines from more manufacturers are achieving WHO Pre-qualification, with areas of focus including the contributions to a Polio-free world, ending cholera, and tackling re-emerging diseases, such as measles. An increase by 50% of number of manufacturing companies holding WHO prequalified vaccines was observed from 2013 to 2019, strengthening open competitiveness for global vaccines supply. Notably, Network members have 181 vaccine projects in the research and development pipeline, highlighting novel vaccines against mosquito-borne diseases, such as dengue, chikungunya and Zika, novel human papillomavirus and pneumococcal conjugated vaccines. This report summarizes the progressive efforts of DCVMN members to contribute to reducing the burden of infectious diseases globally and details their commitment to vaccine innovation, particularly in the past five years, in the context of how vaccine innovations of today will shape the fight against infectious diseases tomorrow.